Study of Light Production With A Fifty Liter Liquid Argon TPC. Issue 1 (1st November 2022) - Babicz, M.; Bilki, B.; Boran, F.; Dolek, F.; Green, P.; Kose, U.; Nessi, M.; Pietropaolo, F.; Resnati, F.; Szelc, A. M.; Zani, A.
Abstract : The Deep Underground Neutrino Experiment (DUNE) is the next very large scale neutrino science and proton decay experiment. DUNE will consist of large-scale near and far detectors. The core elements of these detector systems are liquid argon Time Projection Chambers (LAr TPCs) and light readout systems. Two prototype far detectors were built and operated at CERN Neutrino Platform and extensive developments are underway for improved and upgraded detectors. In order to evaluate various design alternatives and validate new concepts of light readout related to large-scale LAr detectors, we have performed several experiments with a fifty liter liquid argon TPC at CERN. Among the long list of configurations we probed, study of various wavelength shifters, operation in dual phase mode and Xe and N2 doping under different scenarios can be listed. Here we report on the details of the various test campaigns and discuss our findings and their impact on the design and operational parameters.